O-009 WEB shape modification during follow-up: the bicêtre experience. (4th August 2020) - Caroff, J; Mihalea, C; Ikka, L; Ozanne, A; Gallas, S; Chalumeau, V; Moret, J; Spelle, L
Abstract : Purpose: WEB device shape modification (WShM) is a potential cause of poor angiographic outcome during follow-up, despite an initial complete aneurysmal occlusion. The prevalence, the factors affecting WShM and the ways to prevent this phenomenon are only partially established. Materials and Methods: Patients treated in Bicêtre hospital with a WEB device between were included October 2015 and January 2019. Exclusion criteria were the lack of follow-up or a combined treatment. Thanks to rotational cone-beam CT (CBCT) acquisitions, systematically performed after implant and during follow-up, we have analyzed WEB morphology over time. WshM was correlated with anatomical and procedures parameters. Angiographic occlusion was evaluated according to the Bicêtre occlusion scale (BOSS). Results: 92 aneurysms were treated with a WEB device and 68% were finally included in this register. 87% of WEB devices presented WShM during follow-up (at least 20% of height reduction). We did not find a direct relationship between the extent of WShM and occlusion rates. But in the worsening occlusion group the average WShM was significantly higher than in the stable occlusion group (50% vs 43%, p<0.01). WEB width oversizing at implant was significantly associated with a reduced WShM rate. Conclusion: CBCT allowed us to perform the first precise and quantitative analysis of WEB shape modification during follow-up. WShM is a very frequent phenomenon, negatively affecting occlusion rates. But it can be partly overcome with an appropriate oversizing strategy. Disclosures: J. Caroff: None. C. Mihalea: None. L. Ikka: None. A. Ozanne: None. S. Gallas: None. V. Chalumeau: None. J. Moret: None. L. Spelle: None.